Assessment and multimodal management of pain (New York Foster Academics, 2023)
Pain refers to an emotional experience and unpleasant sensation commonly caused by tissue damage. It enables the body to respond and prevent any further damage. Acute pain and chronic pain are the two primary types of pain. Acute pain is a typical reaction to an illness or injury. It usually begins abruptly and is short-lived. Chronic pain lasts longer than the anticipated period for recovery. It usually lasts longer than three months. The initial assessment of pain generally starts with a physical examination. Pain is measured by determining its impact on activities like work, mood, sleep and relationships. Complementary therapies, pain medications, and physical therapy are major therapies for the effective management of pain. The multimodal management of pain includes relying on multiple therapies and medications for pain management. Some of the groups of medications, which are used in combination for managing pain are alpha-2 agonists, local anaesthetics, NSAIDs, opioids and acetaminophen. This book is a detailed explanation of pain assessment and multimodal management. It is a resource guide for experts as well as students.
Keywords: Pain; Pain- Physicological Aspects; Pain Medicine; Hunt, Lily ed